Modern Clinical Practice: Pros and Cons of Treatment Alfacalcidol for Patients with Osteoporosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Currently, medications used to treat osteoporosis (OP) have been shown to be effective in reducing the risk of fractures in multicenter placebo-controlled studies. These are primarily bisphosphonates and denosumab (antiresorptive agents), teriparatide (a bone anabolic) and strontium ranelate (a drug with a dual mechanism of action). For primary prevention of the disease and as part of combination therapy for AP, calcium and vitamin D are used. Among vitamin D preparations, its active metabolites occupy a special place, one of which is alfacalcidol - 1α(OH)D3. When ingested, it is hydroxylated in the liver by 25-hydroxylase and converted into D-hormone, or calcitriol (1α,25(OH)2D3). The mechanism of action of the drug is the binding of 1α, 25(OH)2D3 with vitamin D receptors in target organs. In the intestines, this leads to an increase in the absorption of calcium and phosphorus, and in the kidneys, to an increase in the reabsorption of calcium in them.